The Strategic Leadership Role of Foundation Leaders in Improving the Quality of Education at Various Levels Education: Case Study on Bi Ashokal Hajar Foundation - Senandung A.S, Al Jabar L; Pasaribu, Veta Lidya Delimah (Manager : Jurnal Ilmu Manajemen, 2024)
This study aims to identify and evaluate the leadership strategies applied by the leadership of the Bi Ashokal Hajar Foundation in improving the quality of education at various levels of education. The research used a qualitative approach with descriptive methods, involving observation, in-depth interviews and documentation. The results show that the strategic leadership applied by the foundation leaders has a positive impact on the quality of education. Foundation leaders are able to direct, motivate and create a conducive working environment, which contributes to improving staff performance and loyalty as well as education quality. Support for educators' innovation and professional development is also a key factor in achieving higher educational goals. Recommendations provided by respondents highlighted the importance of improving learning facilities, developing training programs and effective communication between leaders and staff. This research provides valuable insights for other educational institutions in optimizing the role of strategic leadership to improve education quality. The findings are in line with previous research that emphasizes the importance of effective leadership styles and a supportive work environment in improving educational performance and quality